The safe handling of chemicals in industry; Vol.3 - Phillip A Carson (Longman, 1988)
The book provides more detailed guidance on the application of the general principles by reference to selected examples. Additional material is included on controlling the environmental impact of chemicals, controlling microbiological hazards, chemical hazards in the consumer market, emergency planning, the role of ergonomics and communication in accident causation and prevention, and the economics of safety and loss prevention